2017
DOI: 10.1002/bit.26463
|View full text |Cite
|
Sign up to set email alerts
|

A novel, smaller scaffold for Affitins: Showcase with binders specific for EpCAM

Abstract: Affitins are highly stable engineered affinity proteins, originally derived from Sac7d and Sso7d, two 7 kDa DNA-binding polypeptides from Sulfolobus genera. Their efficiency as reagents for intracellular targeting, enzyme inhibition, affinity purification, immunolocalization, and various other applications has been demonstrated. Recently, we have characterized the 7 kDa DNA-binding family, and Aho7c originating from Acidianus hospitalis was shown to be its smallest member with thermostability comparable to tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Previous studies with Sul7d proteins (Kalichuk et al, ), including Sac7d and Aho7c, described the generation of Affitins against purified proteins by using ribosome display as a selection tool (Béhar et al, ; Béhar et al, ; Correa et al, ; Kalichuk et al, ; Mouratou et al, ). In this work, a total of seven rounds of ribosome display were performed to select Sac7d‐based Affitins (Figure a) with specificity for S. aureus using the library L1 (Mouratou et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies with Sul7d proteins (Kalichuk et al, ), including Sac7d and Aho7c, described the generation of Affitins against purified proteins by using ribosome display as a selection tool (Béhar et al, ; Béhar et al, ; Correa et al, ; Kalichuk et al, ; Mouratou et al, ). In this work, a total of seven rounds of ribosome display were performed to select Sac7d‐based Affitins (Figure a) with specificity for S. aureus using the library L1 (Mouratou et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Using combinatorial engineering against proteins from bacterial, animal, and human origins, we have generated a number of Affitins, which show specificity and affinity for their protein targets in nanomolar and subnanomolar ranges. They are small (7 kDa), highly thermostable (up to 90°C), pH‐stable (from 0 up to 13), highly soluble, well‐produced in E. coli grown in flasks (up to 200 mg/L culture) and can be easily engineered (Béhar et al, ; Béhar, Pacheco, Maillasson, Mouratou, & Pecorari, ; Buddelmeijer, Krehenbrink, Pecorari, & Pugsley, ; Kalichuk et al, ; Krehenbrink et al, ; Miranda, Brient‐Litzler, Zidane, Pecorari, & Bedouelle, ; Mouratou et al, ; Pacheco, Behar, Maillasson, Mouratou, & Pecorari, ; Pecorari & Alzari, ). Furthermore, we have shown that Affitins are well‐suited for detection, capture, and inhibition applications for which protocols can require harsh conditions of pH, temperature or a dry condition (Béhar, Renodon‐Cornière, Mouratou, & Pecorari, ; Cinier et al, ; Correa et al, ; Fernandes et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, affitins have the potential to cover and/or deeply penetrate active sites [149]. In order to further improve on the properties of affitins, Aho7c originating from Acidianus hospitalis , possessing picomolar affinities (K d of 110 pM), high stability (up to 74 °C; pH 0–12), and a 10% smaller size (60 compared to 66 amino acids) has been characterized [152]. However, despite the constant development of the small-size affitins, they have yet to undergo significant clinical testing to evaluate their safety and efficacy.…”
Section: Alternative Binding Scaffoldsmentioning
confidence: 99%
“…Epithelial cell adhesion molecule (EpCAM, CD326; Chaudry et al, 2007;van der Gun et al, 2010;Seeber et al, 2016;Vazquez-Iglesias et al, 2019) and human epidermal growth factor receptor 2 (HER2, CD340; Siena et al, 2018;Gbolahan and O'Neil, 2019;Li et al, 2019) are relevant tumour associated transmembrane glycoprotein receptors in CRC. Their importance has resulted in the development of several high-affinity protein binders, including designed ankyrin repeat proteins (DARPins; Stefan et al, 2011) and affitins against EpCAM (Kalichuk et al, 2018), and affibodies against HER2 (Orlova et al, 2006;Feldwisch et al, 2010). Recently, the potential of tumour-targeted gene knockdown using EpCAM aptamer has been reported for management of aggressive breast cancers (Zhang et al, 2021), while DARPins against HER2 and EpCAM were fused with toxins and combined to effectively prevent the tumour escape (Shramova et al, 2020).…”
Section: Introductionmentioning
confidence: 99%